Deification in classical Greek philosophy and the Bible - Murphy, James Bernard (Cambridge University Press, 2024)
"The goal of human life, according to Plato, Aristotle, and the Bible, is to become as much like god as possible. This book, written in vivid and lucid English, illuminates Greek philosophy by showing how it grows out of ancient Greek religion and how it compares to biblical religion"